Image log analysis of in situ stress orientation, breakout growth, and natural geologic structures to 2.5 km depth in central Scandinavian Caledonides: Results from the COSC‐1 borehole. Issue 5 (13th May 2017) - Wenning, Quinn C.; Berthet, Theo; Ask, Maria; Zappone, Alba; Rosberg, Jan‐Erik; Almqvist, Bjarne S. G.
Abstract: Stress‐induced borehole deformation analysis in the Collisional Orogeny in the Scandinavian Caledonide deep scientific borehole establishes in situ stress orientation in a poorly characterized region in central Sweden. Two acoustic televiewer logging campaigns, with more than 1 year between campaigns, provide detailed images along the full length of the 2.5 km deep borehole for breakout, drilling‐induced tensile fracture (DITF), and natural occurring structural analysis. Borehole breakouts occur in 13 distinct zones along total length of 22 m, indicating an average maximum horizontal stress, S Hmax, orientation of 127° ± 12°. Infrequent DITFs are constrained within one zone from 786 to 787 m depth ( S Hmax orientation: 121° ± 07°). These S Hmax orientations are in agreement with the general trend in Scandinavia and are in accordance with many mechanisms that generate crustal stress (e.g., ridge push, topographic loading, and mantel driven stresses). The unique acquisition of image logs in two successions allows for analysis of time‐dependent borehole deformation, indicating that six breakout zones have crept, both along the borehole axis and radially around the borehole. Strong dynamic moduli measured on core samples and an inferred weak in situ stress anisotropy inhibit the formation of breakouts and DITFs. Natural fracture orientation below 800 m is congruent to extensional or hybrid brittle shear failure along the same trend as the current S Hmax . Analysis of foliation in the image logs reinforces the interpretation that the discontinuous seismic reflectors with fluctuating dip observed in seismic profiles are due to recumbent folding and boudinage. Plain Language Summary: Knowledge of the in situ stress state gives information on dynamic processes, for example, earthquakes within the Earth, and is also applied to various geotechnical drilling and excavation projects. This paper analyzes stress‐induced deformation features in image logs that span the length of the 2.5 km deep borehole in Central Scandinavia, to address the subsurface stresses in the region. We identified a stress orientation in the borehole that is oriented parallel to the general trend in Scandinavia. This orientation is compatible with many drivers of stresses including pushing and pulling forces on the sides from the crust, gravitational loading from mountain ranges, and driving below due to flow of the mantle. A unique observation from this study is that some breakouts have grown both along and radially around the borehole wall. Such radial breakout growth around the borehole will affect how the magnitude of subsurface stresses is estimated. Key Points: Borehole breakouts develop sporadically and indicate NW‐SE maximum horizontal stress orientation aligned along the 2.5 km borehole Breakout growth is observed in overlapping logging intervals Natural fracture strike orientations are generally aligned with the maximum horizontal stress orientation